"Ethical way of conducting business of e-commerce companies during COVID19 pandemic - An investigation of e-commerce shoppers of Pune" - Dr. Vivek Swami, Dr. V. R. Humbe (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Since March 2020, India has seen the surge in COVID19 infection throughout the various sections of the society across all states and union territory. The COVID19 pandemic has affected all sectors in India. During the lockdown, migrant laborers went back to their own native places resulting in stoppage of manufacturing, assembling, trading and construction activities. The pandemic also affected the trade. Many of the middle level channel and e-commerce establishments faced the problem of delivery transactions. Due to wide spread of the corona virus in the society, government at center and at state took a decision of lockdown in the regular activities with a purpose of breaking the chain of spreading the virus. These trade establishments have forced to look into new ways to complete their transactions.